Pola Perilaku Pembelian Produk Apparel untuk Balita oleh Millennial Moms dan Implikasinya untuk Pemasar Kids Apparel - Gunawan, Annetta; Muchardie, Brian Garda (Bina Nusantara University, 2015)
The phenomenon that recently occurred is the height of the millennial moms busy uploading pictures ofÂ their children in such a way they dressed through various social media. Accordingly, the need of the millennialÂ moms in dressing their children up is related to the shopping patterns in kids apparel products. Buying kidsÂ products, especially apparel, not only meets the needs, but it is also the pleasure of the millennial mom. TheÂ unique characters of the millennial moms behavior that differ from the motherâs of previous generations, makeÂ kids apparel marketers need to focus on the overall process of purchasing decisions made by the millennialÂ moms. The purpose of this qualitative study is to explore the patterns of behavior of the millennial moms whenÂ shopping apparel products for toddlers, including the factors that influence the need awareness, informationÂ search, evaluation of alternatives, purchase behavior, and behavior post-purchase stages. Data collectionÂ method used is depth interview since the purpose of this exploratory study is to gain insight and understandingÂ of consumers about a particular topic. The results of this study include an explanation of shopping behaviorÂ shown by the millennial moms for kids apparel products in all stages of the purchase decision process, shoppingÂ typology of millennial moms in kids apparel products, as well as the implications for marketers.